Information Vigilance as a Mechanism to Enhance the Mental Image of the Institution - Menasri Nassima; Hadj Salem Attia (Kurdish Studies, 2024)
Practicing the digital information vigilance through vigilance over image and analyzing the social media networks enables the institution to acquire indicators and informational cues sourced from its digital environment. This helps in determining the potential impact on its mental image. Accordingly, this article aims to highlight the contribution of digital vigilance, represented by image vigilance and social media analytics, in enhancing the institution's mental image by monitoring and analyzing diverse informational content circulated across social networks. This research paper concludes that effective reading and strategic utilization of audience interactions and comments accompanying posts about or from the institution enable it to measure its image as a preliminary stage. This naturally fits within the contexts of conducting image studies, subsequently deriving focal points for future enhancement.